PEMEROLEHAN BAHASA INDONESIA TATARAN KELAS KATA PADA ANAK USIA EMPAT TAHUN - Saadatun Nahariyah (BASA Journal of Language & Literature, 2022)
The focus of the study of this research is the acquisition of the Indonesian language of the research subjects by paying attention to language production at the word class level of the subjects. The approach used in this study is descriptive qualitative because it intends to understand phenomena about the experiences of research subjects such as behavior, perceptions, motivations, actions, and others by way of descriptions in the form of words in a special or natural context with natural methods. The data collection technique used was the transcription of the recording results, and interviews with informants who were the subject's family. The form of data is in the form of transcription results and additional notes. The analysis technique in this study was carried out by recording transcripts and recording observations in the field, then coded to make it easier to track data, collect and classify data, then find patterns and relationships. The results of the study show that in the context of playing and carrying out daily activities at home, five types of word classes have been found that have been produced by the subject, namely verbs, nouns, adjectives, pronouns, and numerals. The production of word classes which are mostly produced are verbs and nouns, while the word classes of adjectives, pronouns, and numerals are still little produced. On the basis of the results of these observations, the subject can be classified as a child who has a speech delay, because he has not mastered the construction of sentences using particles and conjunctions as a complement.